2018
DOI: 10.3889/oamjms.2018.432
|View full text |Cite
|
Sign up to set email alerts
|

S100B Serum Level as a Mortality Predictor for Traumatic Brain Injury: A Meta-Analysis

Abstract: BACKGROUND:The pathogenesis of inflammatory neuronal cell damage will continue after traumatic brain injury in which contributed to subsequent mortality. Serum S100B levels were shown to be an early predictor of mortality due to traumatic brain injury.AIM:This Meta-Analysis will analyse the mean and diagnostic strength of serum S100B levels between survived and died subjects with head injuries based on the various follow-up times of nine studies.METHODS:We conducted a meta-anelysis in accordance with PRISMA gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…To date, several analyses have been reported on the usability of S100B protein levels in assessing the severity of TBI [ 41 44 ]. However, none performed a combined analysis of the levels of S100B protein, Gosling's pulsatility index, and jugular venous oxygen saturation for the prediction of mortality and morbidity among patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several analyses have been reported on the usability of S100B protein levels in assessing the severity of TBI [ 41 44 ]. However, none performed a combined analysis of the levels of S100B protein, Gosling's pulsatility index, and jugular venous oxygen saturation for the prediction of mortality and morbidity among patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies imply the negative role of S100B in TBI and represent that S100B in CSF, as an astrocytic protein specific to the central nervous system and a useful marker in outcome prediction for TBI [ 199 , 200 ]. Thus, S100 s protein have been established as useful marker for inflammatory diseases and blood brain barrier damage, which plays an important role in the development and recovery of normal CNS after injury [ 201 – 203 ]. Recently, results of a meta-analysis showed a significant difference in S100B levels between survived and died subjects with head injuries on overall follow-up timeline, during treatment, or 6 months with an average threshold value that varies according to the study method used [ 203 ].…”
Section: Dampsmentioning
confidence: 99%
“…Thus, S100 s protein have been established as useful marker for inflammatory diseases and blood brain barrier damage, which plays an important role in the development and recovery of normal CNS after injury [ 201 – 203 ]. Recently, results of a meta-analysis showed a significant difference in S100B levels between survived and died subjects with head injuries on overall follow-up timeline, during treatment, or 6 months with an average threshold value that varies according to the study method used [ 203 ]. In terms of other S100 proteins and nervous injury, following peripheral nerve injury an immediate acute immune response distally and proximally to the lesion site with rapid transcriptional activation of S100a8 and S100a9 genes resulting in S100A8/A9 hetero- and homodimers has been observed [ 204 ].…”
Section: Dampsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding S100 calcium binding protein B (S100B), there have been mixed data on its utility in TBI; Golden et al, 2018 and Kövesdi et al, 2010 found it to predict poor outcomes following severe TBI, whereas Shahim et al, 2016 determined that it was unhelpful in predicting patient outcomes ( Golden et al, 2018 ; Kövesdi et al, 2010 ; Shahim et al, 2016 ). Potential biomarkers for mTBI have likewise been investigated, and plasma/serum levels of NFL, UCH-L1 and tau (a microtubule-associated protein) were observed to be potentially useful ( Joseph et al, 2018 ; Shahim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%